Life Quality of Children Interested in Music - Kabataş, Mustafa (Redfame Publishing, 2020)
Many definitions have been made about music. Soykan (2002 P: 1) defines music as “explaining the effect that it awakens in the audience with stimulation, impression, affect”. According to (Sun et. al., 1969), music is the art of expression with sound and rhythm (Uçan et. al., 1996) is the music as art; It defines as a whole that describes certain situations, phenomena and events in an aesthetic structure with harmonious sounds that are combined with a certain purpose and method, with a certain understanding of beauty, with the contribution of emotions, thoughts, designs and impressions or other reasons. According to (Özer et. al., 1997). The diversity of the definitions about music arises from the existence of music concepts that vary according to the age, culture and individuals in a culture. Developing and gaining music-related behaviors during the upbringing of individuals is through music education. With music education, it is aimed to create musical behavior change in the desired direction in their psychological, cognitive and affective behavior. The behaviors that are tried to be acquired will be possible with a planned and programmed training process (Akbulut Efe et. al., 2006). Today, there are many institutions providing professional or amateur, paid or free music education. In this study, it was made to observe whether there is a change in the quality of life of children who are 10-14 years old, who are interested in music, compared to those who are not. 68 students interested in the same number of music and not attending the study participated in the study. The data of the study were collected by Kid-KINDL quality of life scale and family questionnaire. The findings were discussed and the study was thought to contribute to the field.
Keywords: 4. Education; 10. No inequality